Accurate and rapid reconditioning of spaced responding - Reynolds, G. S. (1964)
The performance maintained by reinforcing responses only when they terminated interresponse times (IRTs) of 20 sec or greater (DRL schedule) was almost the same during the first session of reconditioning as before extinction. As few as two reinforcements accurately reinstated both the pre-extinction rate of responding and the function relating the duration of an IRT to its conditional probability of occurrence (IRTs/op).